RESPON TERNAK AYAM BROILER TERHADAP RANSUM DENGAN LEVEL POLLARD YANG BERBEDA DAN DISUPLEMENTASI MULTI ENZIM - Emanuel Luan; Catootjie Lusje Nalle; Bernadus Ndoen (Politeknik Pertanian Negeri Kupang, 2021)
The objective the present research was to evaluate the response of broilers fed maize-pollard diets supplemented with multi enzymes.A total of 240 broiler chicks were randomly distributed to 240 pens (10 birds/pen). The experimental design used was a 3 x 2 factorial completed randomized design with the main factors pollard level and enzymes (-,+). The results showed no pollard level (PL) x multi enzyme (ME) interaction (P > 0,5 - 0,01) on the growth performance of birds. Pollard level only affected (P<0.01) the body weight gain (BWG) of birds. Birds fed multi enzymes had better (P<0.05-0.01)feed intake (FI) and (BWG) than those who fed without enzymes. The FI of birds fed ME was higher (P<0.05) than those fed no enzymes. Pollard (10 and 15%) increased (P<0.05) the BWG. In conclusion, the multi enzymes in the diets containing different level of pollard improve the performance of birds. Key Words: Broiler, Enzyme, Pollard, Performance